2014
DOI: 10.3171/2014.5.spine13549
|View full text |Cite
|
Sign up to set email alerts
|

Leakage detection on CT myelography for targeted epidural blood patch in spontaneous cerebrospinal fluid leaks: calcified or ossified spinal lesions ventral to the thecal sac

Abstract: Object The purpose of this study was to describe significant CT myelography findings for determination of the leak site and outcome of targeted epidural blood patch (EBP) in patients with spontaneous CSF leaks. Methods During 2005–2013, spontaneous CSF leaks were diagnosed for 12 patients with orthostatic headaches. The patients received targeted EBP on the basis of CT myelography assessments. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 17 publications
(22 reference statements)
1
27
0
3
Order By: Relevance
“…Various clinicians subsequently reported the efficacy of epidural blood patch at non‐targeted lumbar levels . Recent studies have demonstrated that targeted EBP at the site of a presumed leak point achieves better outcomes than non‐targeted methods . Thus, based on the existing literature, most of the patients with SIH could be treated with these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinicians subsequently reported the efficacy of epidural blood patch at non‐targeted lumbar levels . Recent studies have demonstrated that targeted EBP at the site of a presumed leak point achieves better outcomes than non‐targeted methods . Thus, based on the existing literature, most of the patients with SIH could be treated with these methods.…”
Section: Discussionmentioning
confidence: 99%
“…2 Spondylotic spurs and herniated discs have also been implicated as causative factors. 7 Although EBP provides persistent relief in 61% to 75% of patients with postdural puncture headache, 8 Sencakova et al 9 found that only 36% of subjects with SIH responded to EBP. However, these authors observed another 20% of patients improved after a second EBP and 16% after multiple attempts.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic visualization of CSF outflow using imaging studies may be helpful and may provide evidence of CSF leakage at that particular level. Although the importance of dynamic digital subtraction myelography and CT myelography in identifying the CSF leakage point has been recognized,[91318] they present the major disadvantage of increased radiation exposure. In this context, identifying leakage points with MRI is beneficial in reducing the risk.…”
Section: Discussionmentioning
confidence: 99%